Redefining Economic Efficiency in Islamic Economics: A Maqasid-Based Approach to Sustainable Development Goals - Surya, Ade Anastasya; Khadiq, Indi Najmu; Marhamah, Layinatul; M. Djidin (Bertuah Jurnal Syariah dan Ekonomi Islam, 2025)
The concept of efficiency in conventional economics is generally interpreted as an effort to maximize output with minimal resource use. This approach tends to be oriented solely toward instrumental rationality and economic growth, without comprehensively considering ethical dimensions, distributive justice, and ecological sustainability. On the other hand, the Sustainable Development Goals (SDGs) agenda demands a development paradigm that is not only economically efficient but also socially just and environmentally sustainable. This article aims to reconstruct the concept of efficiency in Islamic economics through the maqasid al-shariah approach and analyze its relevance to achieving the SDGs. This research is a literature review with a conceptual-analytical approach to various primary and secondary sources related to efficiency theory, maqasid al-shariah, and the SDGs framework. The study's findings demonstrate that efficiency from an Islamic economic perspective is not solely oriented toward optimizing resources, but rather toward achieving welfare (maslahah), balance (mīzān), and holistic well-being (falah). Thus, maqasid-based efficiency simultaneously integrates economic, social, and ecological dimensions. This concept is substantive and compatible with the SDGs, particularly in terms of poverty alleviation, inequality reduction, inclusive economic growth, and environmental protection. This study confirms that Islamic economics is not only aligned with the global sustainable development agenda but also offers an ethical-transcendental foundation that enriches the discourse on efficiency in contemporary development theory